CURING EFFICIENCY OF DUAL-CURE RESIN CEMENT UNDER ZIRCONIA WITH TWO DIFFERENT LIGHT CURING UNITS - Pınar GÜLTEKİN; Elif PAK TUNÇ; Değer ÖNGÜL; Volkan TURP; Özgür BULTAN; Burçin KARATAŞLI (Istanbul University, 2015)
Purpose: Adequate polymerization is a crucial factor in obtaining optimal physical properties and a satisfying clinical performance from composite resin materials. The aim of this study was to evaluate the polymerization efficiency of dual-cure resin cement cured with two different light curing units under zirconia structures having differing thicknesses. Materials and Methods: 4 zirconia discs framework in 4 mm diameter and in 0.5 mm, 1 mm and 1.5 mm thickness were prepared using computer-aided design system. One of the 0.5 mm-thick substructures was left as mono-layered whereas others were layered with feldspathic porcelain of same thickness and ceramic samples with 4 different thicknesses (0.5, 1, 1.5 and 2.0 mm) were prepared. For each group (n=12) resin cement was light cured in polytetrafluoroethylene molds using Light Emitting Diode (LED) or Quartz-Tungsten Halogen (QHT) light curing units under each of 4 zirconia based discs (n=96). The values of depth of cure (in mm) and the Vickers Hardness Number values (VHN) were evaluated for each specimen. Results: The use of LED curing unit produced a greater depth of cure compared to QTH under ceramic discs with 0.5 and 1 mm thickness (p<0.05).At 100μm and 300 μm depth, the LED unit produced significantly greater VHN values compared to the QTH unit (p<0.05). At 500 μm depth, the difference between the VHN values of LED and QTH groups were not statistically significant. Conclusion: Light curing may not result in adequate resin cement polymerization under thick zirconia structures. LED light sources should be preferred over QTH for curing dual-cure resin cements, especially for those under thicker zirconia restorations.